Persistent Occurrence of Cryptosporidium hominis and Giardia duodenalis Subtypes in a Welfare Institute - Wang, Yuanfei; Li, Na; Guo, Yaqiong; Wang, Lin; Wang, Rui; Feng, Yaoyu; Xiao, Lihua (Frontiers in Microbiology, 2018)
Few data are available on the transmission dynamics of intestinal protozoa in children in welfare institutes. In this study, fecal specimens were collected from 396 children in a welfare institute in Shanghai, China during December 2011 (207 specimens), June 2012 (78 specimens) and September 2013 (111 specimens), and examined for Cryptosporidium spp., Giardia duodenalis, and Enterocytozoon bieneusi by PCR analysis of the small subunit rRNA, triosephosphate isomerase, and internal transcribed spacer genes, respectively. The Cryptosporidium hominis and G. duodenalis assemblage A identified were further subtyped by multilocus sequence typing. Altogether, Cryptosporidium was detected in 39 (9.8%) children, with infection rates of 11.6% (24/207), 9.0 % (7/78) and 7.2% (8/111) in December 2011, June 2012 and September 2013, respectively. Infection rates were higher in children of 0-12 months (20.4% compared to 0-7.3% in other age groups, P = 0.0001) and those with diarrhea (17.9% compared to 7.7% in those with no diarrhea, P = 0.006). In contrast, G. duodenalis was detected in 161/396 (40.7%), with infection rates of 48.3% (100/207), 35.9% (28/78) and 29.7% (33/111) in December 2011, June 2012 and September 2013, respectively. There were no significant gender- or diarrhea-associated differences, but the G. duodenalis infection rate in children of 13-24 months (50%) was significantly higher than in the age groups of 0-12 months and >48 months (29.8%-36.5%, P = 0.021). Co-infection of Cryptosporidium and G. duodenalis was seen in 19 (4.8%) children, but no E. bieneusi infection was detected in this study. All Cryptosporidium-positive specimens belonged to the subtype IaA14R4 of C. hominis, while all G. duodenalis-positive specimens belonged to sub-assemblage AII. Both were the same subtypes in a previous outbreak of cryptosporidiosis and giardiasis in a hospital ward hosting children from the welfare institute. Results of the study indicate that there was a persistent occurrence of limited C. hominis and G. duodenalis subtypes in the small enclosed community, with differences in age distribution and association with diarrhea occurrence between cryptosporidiosis and giardiasis.